RELEVANSI ASESMEN FORMATIF BERBASIS GAYA BELAJAR DALAM PEMBELAJARAN TEKS BAHASA INDONESIA: KAJIAN LITERATUR - Bella Puspita; Lailatul Mutia Alda; Abdurahman; Amril Amir (STKIP Subang, 2026)
This study analyzes the relevance of formative assessments that focus on learning styles in teaching Indonesian language texts. The diversity of visual, auditory, and kinesthetic learning styles of students requires a responsive and flexible assessment approach, particularly within the Merdeka Curriculum framework, which emphasizes differentiated learning. The method used was a literature review collected from relevant journal articles, books, and policy documents published in the last five years. The results indicate that formative assessments designed to align with students' learning modalities are consistently associated with increased engagement, motivation, and learning achievement. However, their implementation still faces challenges in the form of teacher competency and the lack of operational technical guidelines. These findings emphasize the importance of developing a contextual and applicable learning style-based formative assessment model in teaching Indonesian language texts.